2016
DOI: 10.1137/140996112
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Definiteness via Shrinking, with an Application to Correlation Matrices with a Fixed Block

Abstract: Abstract. Indefinite approximations of positive semidefinite matrices arise in various data analysis applications involving covariance matrices and correlation matrices. We propose a method for restoring positive semidefiniteness of an indefinite matrix M 0 that constructs a convex linear combination S(α) = αM 1 + (1 − α)M 0 of M 0 and a positive semidefinite target matrix M 1 . In statistics, this construction for improving an estimate M 0 by combining it with new information in M 1 is known as shrinking. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Anther possible use of the MaxDet solution E is to compute the smallest α ∈ [0, 1] such that αE yields a positive semidefinite completion, or equivalently the smallest α ∈ [0, 1] such that (1−α) Σ +αΣ is positive semidefinite. This is precisely the method of shrinking [15] with initial matrix Σ and target matrix the MaxDet completion. The optimal α is 2 α * = 3.4908 × 10 −2 ; it gives α * E F = 3.0148 × 10 −2 and a completion with determinant 3.3809 × 10 −16 and eigenvalues This comparison emphasizes that the MaxDet completion is very different from the nearest correlation matrix, and that through shrinking it can yield a completion not much further from Σ than the nearest correlation matrix.…”
Section: Numerical Examplementioning
confidence: 99%
“…Anther possible use of the MaxDet solution E is to compute the smallest α ∈ [0, 1] such that αE yields a positive semidefinite completion, or equivalently the smallest α ∈ [0, 1] such that (1−α) Σ +αΣ is positive semidefinite. This is precisely the method of shrinking [15] with initial matrix Σ and target matrix the MaxDet completion. The optimal α is 2 α * = 3.4908 × 10 −2 ; it gives α * E F = 3.0148 × 10 −2 and a completion with determinant 3.3809 × 10 −16 and eigenvalues This comparison emphasizes that the MaxDet completion is very different from the nearest correlation matrix, and that through shrinking it can yield a completion not much further from Σ than the nearest correlation matrix.…”
Section: Numerical Examplementioning
confidence: 99%
“…Let A ∈ R n×n be symmetric with unit diagonal and eigenvalues The next result gives a sharper upper bound than (3.5). The proof uses the idea of shrinking from Higham, Strabić, andŠego [17].…”
Section: Existing Boundsmentioning
confidence: 99%
“…The rate of convergence of this method is at best linear but we have recently shown that the convergence can be accelerated significantly using Anderson acceleration [16]. The alternating projections method remains widely used in applications (see, for example, the references in [16], [17]), though a faster, globally quadratically convergent Newton algorithm was later developed by Qi and Sun [24], to which practical improvements were made by Borsdorf and Higham [6]. The algorithm of Borsdorf and Higham requires an eigendecomposition of a symmetric matrix on each iteration and so it costs at least 10n 3 /3 flops per iteration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Projection of symmetric or Hermitian matrices to the positive semidefinite cone is a standard operation that arises frequently in scientific computing. A common, practical, example is restoring positive definiteness of partially unknown or corrupted correlation matrices [17] arising in e.g., economics [12], integrated circuit design [20] and wireless communications [11]. Further, more generic, examples include quasi-newton optimization methods [7, §4.2.2], incomplete matrix factorizations of sparse matrices [5, §15.11] and, finally, first order methods for solving semidefinite problems (SDPs) [2,19] which, as we proceed to explain, was the motivating example for this work.…”
Section: Introductionmentioning
confidence: 99%